The Firestone Singing Color Fountain and Multi-Plane Shadow Sign. Only Installations of their Kind in the World, A Century of Progress (R.R. Donnelley & Sons Co.)
Beneath the misty fountain domes is a battery of colored lights. As the music fills the garden, the varying wave lengths come in contact with delicate mechanism, which connects the colored lights. The result is an ever-changing array of beautiful color combinations playing upon the fountains in perfect harmony with the music. The Firestone multi-color shadow sign is constructed of shadow planes behind which are thousands of incadescent bulbs, reflecting an ever-changing combination of beautiful pastel shades of blue, gree, orange, and yellow.